6-C-Methyl Flavonoids Isolated from Pinus densata Inhibit the Proliferation and Promote the Apoptosis of the HL-60 Human Promyelocytic Leukaemia Cell Line - Yue, Rongcai; Li, Bo; Shen, Yunheng; Zeng, Huawu; Li, Bo; Yuan, Hu; He, Yiren; Shan, Lei; Zhang, Weidong (Planta Medica, 2013)
Three structurally related 6-C-methyl flavonoids isolated from Pinus densata, including 5,4′-dihydroxy-3,7,8-trimethoxy-6-C-methylflavone (PD1), 5,7,4′-trihydroxy-3,8-dimethoxy-6-C-methylflavone (PD2), and 5,7,4′-trihydroxy-3-methoxy-6-C-methylflavone (PD3), were tested for their ability to inhibit the proliferation and promote the apoptosis of the HL-60 human leukaemia cell line. Cytotoxicity assays in the HL-60 human cancer cell line demonstrated that 5,4′-dihydroxy-3,7,8-trimethoxy-6-C-methylflavone exhibited the most potent cytotoxicity of the three structurally related 6-C-methyl flavonoids. 5,4′-Dihydroxy-3,7,8-trimethoxy-6-C-methylflavone inhibited the proliferation of HL-60 cells in a dose-dependent manner with an IC50 of 7.91 µM (48 h treatment). Furthermore, 5,4′-dihydroxy-3,7,8-trimethoxy-6-C-methylflavone-induced apoptosis was associated with mitochondrial membrane disruption and cytochome c release. Flow cytometry analyses revealed an increase in the hypodiploid population in 5,4′-dihydroxy-3,7,8-trimethoxy-6-C-methylflavone-treated HL-60 cells. Treatment with a concentration of 5,4′-dihydroxy-3,7,8-trimethoxy-6-C-methylflavone that induced apoptosis activated caspase-3 but did not activate caspase-1. A caspase-3 inhibitor (Ac-DEVD-CHO), but not a caspase-1 inhibitor (Ac-YVAD-CHO), reversed the cytotoxic effects of 5,4′-dihydroxy-3,7,8-trimethoxy-6-C-methylflavone in HL-60 cells. These data demonstrated that 5,4′-dihydroxy-3,7,8-trimethoxy-6-C-methylflavone effectively induced the apoptosis of HL-60 cells and exhibited significant anticancer activity via the mitochondrial caspase-3-dependent apoptosis pathway.
Keywords: Pinus densata; Pinaceae; apoptosis; HL-60; caspase-3; 6-C-methyl flavonoids